Comparison of the efficacy and safety of remifentanil versus different pharmacological approaches on prevention of etomidate-induced myoclonus: a meta-analysis of randomized controlled trials - Lang B; Zhang L; Li F; Lin Y; Zhang W; Yang C (Dove Medical Press, 2019)
Bingchen Lang,1 Lingli Zhang,1–3 Fengshan Li,1 Yunzhu Lin,1 Wensheng Zhang,4 Chunsong Yang11Department of Pharmacy, West China Second University Hospital, Sichuan University, Chengdu, People’s Republic of China; 2Evidence-Based Pharmacy Center, West China Second University Hospital, Sichuan University, Chengdu, People’s Republic of China; 3Key Laboratory of Birth Defects and Related Diseases of Women and Children, Sichuan University, Ministry of Education, Chengdu, People’s Republic of China; 4Department of Anesthesiology, Laboratory of Anesthesia and Critical Care Medicine, Translational Neuroscience Center, West China Hospital, Sichuan University, Chengdu, People’s Republic of ChinaObjective: Myoclonus was considered as one conundrum in etomidate induction, which led to multiple risks during clinical anesthesia. The present study was conducted to compare the efficacy of pretreatment with remifentanil to different pharmacological approaches on reducing etomidate-induced myoclonus.Methods: We searched PubMed, Embase, Cochrane Library, and China National Knowledge Infrastructure from the inception to October 2018. Randomized controlled trials comparing remifentanil versus other pharmacological approaches in reducing etomidate-induced myoclonus were eligible to be analyzed.Results: Overall, 13 trials with 1,392 patients met with the inclusion criteria. 1) Pretreatment with remifentanil could reduce the incidence of etomidate-induced myoclonus compared to placebo and fentanyl; few differences were found between the use of remifentanil and the use of midazolam: (incidence of myoclonus: 5.56% with remifentanil vs 71.65% with saline, RR=0.08, with 95% CI [0.05, 0.12], P<0.0001; 3.80% with remifentanil vs 13.33% with fentanyl, RR with 95% 0.31 [0.11, 0.86], P=0.02; 46.00% with remifentanil vs 55.45% with midazolam, RR=0.82, with 95% CI [0.64, 1.06], P=0.13). 2) Compared with placebo, pretreatment with remifentanil could reduce the incidence of mild, moderate, and severe myoclonus; compared with midazolam, patients receiving remifentanil experienced lower occurrence of severe myoclonus; compared with fentanyl, pretreatment with remifentanil associated with significant low occurrence of moderate and severe myoclonus. 3) The outcomes also indicated that pretreatment with remifentanil could prevent excessive hemodynamic changes after endotracheal intubation compared to fentanyl.Conclusions: Pretreatment with remifentanil could be considered as one operative option to reduce both incidence and severity of etomidate-induced myoclonus. Compared with fentanyl, it also provides efficacy in preventing excessive hemodynamic changes after endotracheal intubation. However, the best treatment and the proper prophylactic dosage calls for more high quality evidence with large sample size.Keywords: remifentanil, etomidate, myoclonus, meta-analysis, fentanyl, midazolam